(untitled) (Journal of Global Accounting, 2023)
The objective of this study is to determine the effect of sustainability reporting on corporate performance of quoted oil and gas firms in Nigeria. This study adopted time[1]series and cross-sectional analysis of selected oil and gas firms quoted on the Nigerian Stock Exchange as at 31st December 2017 for a period of seven years spanning from 2011 – 2017. This study made use of Ex-Post Facto research design. Data were gotten from secondary sources obtained from fact books, annual reports and accounts of the studied quoted oil and gas companies in Nigeria as at 31st December, 2017. The relevant data obtained were subjected to statistical analysis using Pearson correlation coefficient and multiple regression analysis via E-View 9.0 statistical software. The results of this study revealed that sustainability reporting (proxied by economic, environmental and social performance indices) has a significant positive effect on return on equity, net profit margin and earnings per share at 5% level of significance. The study recommended amongst others the need to adopt standardized Sustainability Index as this will help in putting pressure on companies to pay more attention to their environment and take much more seriously the issues of sustainable development.